2015
DOI: 10.18632/oncotarget.5993
|View full text |Cite
|
Sign up to set email alerts
|

Palbociclib inhibits epithelial-mesenchymal transition and metastasis in breast cancer via c-Jun/COX-2 signaling pathway

Abstract: Palbociclib, a highly selective CDK4/6 inhibitor, has been shown to be a novel anti-tumor agent that suppresses breast cancer cell proliferation. However, its anti-metastasis activity remains controversial. In the present study, we evaluated whether palbociclib prevented breast cancer cell metastasis and revealed its regulatory mechanism. We found that palbociclib inhibited migration and invasion in the breast cancer cells MDA-MB-231 and T47D. The epithelial-mesenchymal transition (EMT) markers, vimentin and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 33 publications
3
54
0
Order By: Relevance
“…A phase II study is evaluating the safety and activity of abemaciclib in hormone receptor (HR) positive BCBM and lung cancer or melanoma with BM 113. Vimentin and Snail, known as the EMT markers, could be downregulated with palbociclib treatment,114 supporting its inhibition of migration and invasion of breast cancer cells. Ribociclib is also being developed along a similar pathway to palbociclib, so FDA named it”breakthrough therapy” based on lots of experiments results.…”
Section: The Mechanism Of Brain Metastasismentioning
confidence: 99%
“…A phase II study is evaluating the safety and activity of abemaciclib in hormone receptor (HR) positive BCBM and lung cancer or melanoma with BM 113. Vimentin and Snail, known as the EMT markers, could be downregulated with palbociclib treatment,114 supporting its inhibition of migration and invasion of breast cancer cells. Ribociclib is also being developed along a similar pathway to palbociclib, so FDA named it”breakthrough therapy” based on lots of experiments results.…”
Section: The Mechanism Of Brain Metastasismentioning
confidence: 99%
“…23 High concentrations of palbociclib were recently used to allow for tissue perfusion, and a significant increase in the percentage of cleaved-caspase 3-positive cells was observed in human HCC samples. Moreover, palbociclib-treated mice showed a remarkable reduction in tumor volume, indicating that palbociclib treatment can be effective against liver tumors in vivo.…”
Section: Palbociclib Promotes Cell Death Of Crc Regardless Of the Prementioning
confidence: 99%
“…COX-2 has also been reported to be associated with EMT and metastasis of tumor cells [17,18]. Notably, previous studies have shown a positive correction between COX-2 expression and cannabidiolic acid [19].…”
Section: Introductionmentioning
confidence: 99%